2019
DOI: 10.1038/s41598-019-42499-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased influence of ENSO on Antarctic temperature since the Industrial Era

Abstract: Under the influence of recent global warming, modulation of frequencies and amplitude of El Niño-Southern Oscillation (ENSO) and its impacts on global climate have become great concerns to the global community. Antarctic climate is sensitive to these changes owing to tropical and Southern Hemispheric (SH) teleconnections. Antarctic surface air temperature (SAT) reconstructed approximately for the past five centuries (~1533 to 1993 CE) based on multiple oxygen isotope (δ 18 O) records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
5
23
0
2
Order By: Relevance
“…Therefore, it is important to identify the climate modes that influenced SH precipitation and RH. Recent study of Rahaman et al (2019) based on multiple δ 18 O ice core records from West and East Antarctica shows that both the regions come under the influence of ENSO and PDO. Further, they have suggested that influence of ENSO on East Antarctic temperature has increased since the beginning of the industrial Era (~1850).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to identify the climate modes that influenced SH precipitation and RH. Recent study of Rahaman et al (2019) based on multiple δ 18 O ice core records from West and East Antarctica shows that both the regions come under the influence of ENSO and PDO. Further, they have suggested that influence of ENSO on East Antarctic temperature has increased since the beginning of the industrial Era (~1850).…”
Section: Resultsmentioning
confidence: 99%
“…However, since atmospheric circulation affects the heat and sea ice distribution along the WAP, especially during springtime (Clem et al, 2016), we expect patterns of ENSO and/or SAM to leave a footprint in our spring sea ice IPSO 25 record. Several studies suggest an enhanced influence of ENSO and SAM on Antarctic temperatures with increasing greenhouse gas concentrations, so their relation to sea ice is a crucial factor for sea ice and climate predictions (Rahaman et al, 2019;Stammerjohn et al, 2008b). For example, atmosphere-oceansea ice interactions impact the WAP strongly through increased northerly winds during an in-phase −ENSO/+SAM mode.…”
Section: Sea Ice Evolution and Large-scale Atmospheric Circulation Pamentioning
confidence: 99%
“…Ding et al, 2011;Schneider et al, 2012;Steig et al, 2013;Bromwich et al, 2013). Furthermore, the near-surface air temperature and precipitation trends observed on the WAIS seem to be linked to the recent deepening of the Amundsen Sea Low (ASL) influencing meridional air mass and heat transport towards West Antarctica (Genthon et al, 2003;Bromwich et al, 2013;Hosking et al, 2013;Burgener et al, 2013;Raphael et al, 2015;. Changes in the absolute depth of the ASL are strongly related to the El Niño-Southern Oscillation (ENSO) and the SAM (Raphael et al, 2015).…”
Section: Introductionmentioning
confidence: 99%